Associated factors to suicidal behavior among graduate students – scoping review protocol (Research, Society and Development, 2020)
Objective: to describe the methodological steps, through the construction of a scope review protocol aiming at the identification of factors associated with suicidal behavior among graduate students. Method of review: Scope review protocol developed considering mainly the guidelines of the Joanna Briggs Institute. An iterative search strategy is proposed in multiple repositories: SCOPUS, LILACS, Medline (Pubmed), Web of Science, CINAHL, PsycINFO, Open Thesis, and CAPES Thesis and Dissertation Bank. The data selection and extraction process will take place through the evaluation of two reviewers acting independently. Presentation and interpretation of results: Results will be presented in tabular and narrative form. Conclusion: This protocol aims to describe the methodological steps for conducting a scoping review, aiming to reduce bias in the search and selection of references, making these criteria clear and uniform among reviewers.